Stop!: there's a snake in your suitcase - Frost, Adam; Chambers, Mark (Bloomsbury Children's London, 2012)
The Nightingale family live on a barge on the canal near London Zoo, and Mum is a vet. When Tom and Sophie find a bag of snakes dumped at the gates of the zoo, a great and exciting adventure begins. Soon they are finding out about the trade in illegal animals and learning how to care for these wonderful creatures. The snakes are carefully housed in the zoo and, just as they are about to be introduced to the many visitors to the reptile house, a desperate race begins to collect some precious antivenin